Tindakan minyak kelapa dara terhadap tulang osteoporosis pascamenopaus: analisis gen Osteoblastogenesis dan antioksidan ( the effects of virgin coconut oil on postmenopausal osteoporotic bone: analyses on osteoblastogenesis and antioxidant genes) - Abdul-Hamid, Shidqiyyah; Muhammad, Norliza; Naina Mohamed, Isa (Universiti Kebangsaan Malaysia, 2016)
Postmenopausal osteoporosis is one of the main health problems in aging women. It was due to several factors including oxidative stress, which can be controlled through intake of antioxidants from food sources. Virgin coconut oil (VCO) is one of the natural product rich in antioxidants and has been proven to protect osteoporotic bone. This study was conducted to gain in-depth understanding on virgin coconut oil’s activity on osteoporosis at molecular level. Thirty two female Sprague-Dawley rats were divided into four groups, namely Sham operated group, ovariectomized control group (Ovx+Ctrl), ovariectomized with VCO treatment (Ovx+ VCO), and ovariectomized with estrogen treatment (Ovx+E). All treatments were administered orally for ten weeks. Bone samples were obtained to examine changes on expression of superoxide dismutase (SOD),glutathione peroxidase (GPX), osteocalcin and runt-related transcription factor 2 (Runx2) genes. The results indicated that rats receiving VCO treatment had experienced significant increments in SOD, GPX and osteocalcin gene expressions compared to the ovariectomized control group, besides the gene expressions of Runx2 which also showed an increment pattern. In conclusion, VCO helps to protect bone in osteoporotic rat model by increasing the expressions of antioxidant genes and genes which increase the osteoblast acitivities.